Safari - Stanton, David L. ([S.l.] : Starcast, 1998)
Witness amongst several other fascinating animals how the red tailed racer of Southeast Asia relies on stealth and concealment to hunt and ambush its prey. Wildlife paradise also presents the legendary Asian tiger and the deadly giant phyton. Also get a close look at hundreds of lesser known species that prey upon others and pound for pound, none are more ferocious or efficient hunters than the predatory invertebrates
Title from title screen
Executive producer, Paul Sharrant ; written by Chris Menrill, John Ross
Host: John Ross
DVD Format
Keywords: Predatory animals; Predation (Biology)